Investigating risk factors for preterm birth in rural Tanzania: a case-control study. (18th April 2012) - D'Cruz, R; Harding, K
Abstract : Background: Preterm birth (before 37 weeks gestation) is the third leading cause of neonatal death in Tanzania and accounts for 28% of neonatal deaths worldwide. Preterm infants are at greater risk of respiratory, gastrointestinal and neurological diseases. Despite significant research in developed countries, there is little known about the causes of preterm birth in many developing countries. This study investigates the association between specific demographic, socioanthropometric, infective and obstetric risk factors and preterm birth in a rural Tanzanian hospital. Methods: This case-control study examined fifteen potential risk factors at Mkomaindo Hospital, Tanzania using questionnaires and medical records. 188 consecutive women were interviewed within 48 hours of delivery. Statistical analysis was performed using chi-square and ANOVA tests and odds ratios. Results: 26.1% of the cohort of 188 women delivered preterm. The seven factors associated with preterm birth were maternal age of 40 years or older (p= 0.01), school non-attendance (p= 0.04), malaria during pregnancy (p=0.03), maternal syphilis (p=0.02), delivery in the preceding 24 months (p=0.046) and history of stillbirth or abortion (p=0.03) or preterm delivery (p=0.02). Conclusions: The prevalence of prematurity in the studied cohort is significantly higher than worldwide estimates. This may be because the study group was at higher risk (only 40% of the population deliver in hospital). The seven risk factors associated with preterm birth correlate with studies undertaken in developed and other African countries. Identification of remedial factors may inform local health and education policy.